Influence of Environmental Concern and Green Packaging Perception on Consumers' Willingness to Pay For FMCG: Green Skepticism as A Mediator - Alfigo Adisari; Raden Johnny Hadi Raharjo (International Journal of Management Science and Information Technology, 2026)
As sustainability concerns grow, FMCG firms have increasingly turned to eco-friendly packaging as part of their green strategy. Yet a gap persists between consumers' pro-environmental attitudes and their actual purchase behavior, since favorable attitudes toward the environment do not always translate into a premium price consumers are willing to pay. Building on this gap, this study investigates how environmental concern and green packaging perception shape FMCG consumers' willingness to pay, with green skepticism examined as a potential mediating pathway. A total of 176 FMCG consumers in Indonesia were recruited through a purposive-sampling procedure to serve as the study's respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that EC and GP directly and positively predict WTP, whereas the indirect pathways through GS were not statistically supported. Notably, GP was found to reduce GS the reverse of what was hypothesized and GS itself showed no significant bearing on WTP. These findings indicate that in the FMCG context, consumers translate environmental concern and green packaging perception directly into willingness to pay, without a meaningful skeptical evaluation process. This study contributes theoretically by identifying the boundary conditions of green skepticism as a mediating mechanism in low-involvement product categories, and offers practical implications for FMCG companies in designing sustainability communication that is directly value-oriented for consumers.